Studies of Penta-Coordinated Complexes of Nickel(II) with Hydrazones - Agarwal, D.K.; Kumar, Dheeraj (Asian Journal of Chemistry, 2010)
The combining ratio is 1:1 in all the complexes. The electronic spectra of [NiC14H11N2O4Cl], [NiC14H11N2O3SCl], [NiC16H13N2O3Cl] complexes show bands in the region 7000–9000, 10000–12000, 15000–17000 and 22000–23,000 cm–1, a characteristic of penta co-ordination assigned to 3B1(F)→3B2(F); 3B1(F)→3E(F); 3B1(F)→3A2(P) and 3B1(F)→3E transitions in order of increasing energy, based on C4v symmetry, and the transitions are related. IR studies indicate the involvement of > C═O, —CH═N and (CONH) groups in coordination.